Description Essay Writing Skills of Grade V Elementary School Students - Azani, Azzahra Putri; Kaltsum, Honest Ummi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to describe the skills of fifth grade students of SD Negeri 2 Wonokarto in writing descriptive essays. Methodology: The research used a qualitative method, focusing on five aspects: (1) content or idea, (2) content organization, (3) grammar, (4) style: writing structure and vocabulary, and (5) spelling and punctuation. The data source was taken from 7 fifth grade students of SD Negeri 2 Wonokarto. Results: The findings showed that the average student scores for each indicator were as follows: content/idea (21.7), content organization (15.8), grammar (14.7), style (11.9), and spelling/punctuation (10.9). Based on the assessment, 5 students (71.4%) were in the good category, and 2 students (28.6%) were in the fair category. Applications/Originality/Value: Students experienced obstacles such as difficulty in expressing ideas, constructing sentences, and applying correct spelling. To improve descriptive writing skills, creative and innovative teaching methods can be applied, including the use of supportive learning media, visits to the library, consistent writing practice, and the provision of structured writing guidelines and spelling exercises.